2015
DOI: 10.1038/ncomms7569
|View full text |Cite
|
Sign up to set email alerts
|

SINE transcription by RNA polymerase III is suppressed by histone methylation but not by DNA methylation

Abstract: Short interspersed nuclear elements (SINEs), such as Alu, spread by retrotransposition, which requires their transcripts to be copied into DNA and then inserted into new chromosomal sites. This can lead to genetic damage through insertional mutagenesis and chromosomal rearrangements between non-allelic SINEs at distinct loci. SINE DNA is heavily methylated and this was thought to suppress its accessibility and transcription, thereby protecting against retrotransposition. Here we provide several lines of eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
84
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(99 citation statements)
references
References 61 publications
15
84
0
Order By: Relevance
“…Alu expression contribution to genome regulation involves multiple mechanisms, and different approaches have been used to study it, including the analysis of RNA polymerase III activity, retrotransposition, noncoding RNAs, Alu mediated adenosine to inosine (A-to-I) RNA editing, and exonization among others (Oler et al 2012;Daniel et al 2015;Tajnik et al 2015;Varshney et al 2015;Klawitter et al 2016;Lin et al 2016;Moráles-Hernandez et al 2016;Nishikura 2016). Therefore, unveiling the specific contribution of each element to genome regulation requires targeted customized studies.…”
Section: Epigenetic and Functional Features Of Transcribed Alu Repeatsmentioning
confidence: 99%
“…Alu expression contribution to genome regulation involves multiple mechanisms, and different approaches have been used to study it, including the analysis of RNA polymerase III activity, retrotransposition, noncoding RNAs, Alu mediated adenosine to inosine (A-to-I) RNA editing, and exonization among others (Oler et al 2012;Daniel et al 2015;Tajnik et al 2015;Varshney et al 2015;Klawitter et al 2016;Lin et al 2016;Moráles-Hernandez et al 2016;Nishikura 2016). Therefore, unveiling the specific contribution of each element to genome regulation requires targeted customized studies.…”
Section: Epigenetic and Functional Features Of Transcribed Alu Repeatsmentioning
confidence: 99%
“…11 Genome-wide analyses suggest that only »0.1% of Alu loci are transcribed or occupied by pol III in the cell lines investigated. [12][13][14] Other studies reported even lower pol III occupancy, [15][16][17] …”
Section: Sine Expression Can Have Detrimental Consequences and Is Submentioning
confidence: 99%
“…Only 24 Alus were bound to Pol III in more than one cell line [33], supporting the hypothesis that Alu elements are controlled by genetic or epigenetic features limiting their expression to a certain state or tissue. As suggested by a recent work combining epigenetic studies with ChIP-bisulphite-sequencing (ChIP-BSSeq) to map the methylation state of Pol III-bound Alus, it is the methylation of H3K9, rather than DNA, that suppresses accessibility of SINEs to the transcriptional machinery [35]. Among the novel Pol III loci, most interesting was the identification in human cells [24] and mouse liver [26] of a conserved antisense MIR (Mammalian Interspersed Repeat) located in the first intron of the POLR3E gene, which encodes the RPC5 subunit of Pol III.…”
Section: Chip-seq Reveals Pol III Binding Dynamics In Multiple Eukarymentioning
confidence: 99%